Civil Liability for Medical Robot Damages According to Artificial Intelligence Applications - Khalid Saleh Alghamdi (International Journal of Law Research and Studies, 2026)
This research examines civil liability for damages arising from the use of medical robots, in light of the rapid development of artificial intelligence technologies and their increasing integration into the healthcare sector, particularly in diagnosis, surgery, treatment, and follow-up care. Medical robots have become an integral part of the healthcare system, raising new legal issues related to defining their legal status and the basis for assigning liability for damages that may result from their use. The research aims to clarify the nature and legal character of medical robots, and to assess the adequacy of traditional rules of civil liability in addressing damages resulting from their use. It also analyzes the shortcomings of tort liability in this field, given the complexity of intelligent systems and the multitude of parties involved in their design and operation. Furthermore, the research addresses the legal basis of strict liability as the most appropriate framework for providing effective protection to the injured party, by requiring proof of damage and causation without necessitating proof of fault. The research employs a comparative fundamentalist approach, examining comparative legislation and jurisprudential trends, particularly French and European law, while also considering the position of the Saudi legal system. The research concluded that medical robots currently lack independent legal personality, and that liability should be directed at the parties benefiting from these technologies, according to the principle of shared responsibility. The research also addressed the implications of civil liability, particularly concerning compensation for bodily harm, and innovative alternatives to compensation, such as mandatory insurance and compensation funds, as complementary mechanisms that ensure the injured party is not deprived of their right to compensation and achieve a balance between protecting patients and encouraging medical innovation.